Gravity and Magnetic Constraints on the Crustal Structure of the Ceará Plateau, Brazilian Equatorial Margin - Moura, Denise Silva de; Molina, Eder Cassola; Marangoni, Yara Regina; Jovane, Luigi (Frontiers in Earth Science, 2019)
The Brazilian Equatorial Margin (BEM) is a transform passive margin with long fracture zones and several seamounts, including the largest one, the Ceará Plateau (CP). This is a complex and poorly studied area, with few available geophysical data. Gravity and magnetic data from the Equant I Project, seismic published lines and other previous studies are used to make several models and analyses. We related the basement, internally comprised of two magmatic highs, to gravity and magnetic anomalies since there are a positive density and susceptibility contrast between sedimentary and basement rocks. Through gravity and magnetic forward modeling, we estimated the basement surface between 800 and 6000 m and the Mohorovičić discontinuity about 22–23 km below the CP. We also present and discuss the position of the continent-ocean boundary 40 km away from the continental shelf, placing the plateau at the oceanic crust domain, and the area of the transitional crust, with an extension of 40–50 km, formed during the rifting phase of the Atlantic Ocean opening.